2009
DOI: 10.1007/s00417-009-1058-x
|View full text |Cite
|
Sign up to set email alerts
|

Combinatory inhibition of VEGF and FGF2 is superior to solitary VEGF inhibition in an in vitro model of RPE-induced angiogenesis

Abstract: RPE from CNV patients expresses angiogenic growth factors that act in part independently of VEGF. Targeted combinatory therapy can be superior to solitary anti-VEGF therapy. One possible candidate for combinatory therapy is FGF2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 32 publications
2
27
0
Order By: Relevance
“…Studies about the role of FGF-2 in the de-velopment of CNV showed that FGF-2 can indirectly induce the neovascularisation formation via upregulation of VEGF and increasing the proliferation of endothelial cells [43][44][45] . Stahl et al [26] reported that combined inhibition of VEGF and FGF-2 was a superior therapy compared to single inhibition of VEGF in the treatment of CNV. Hu et al [27] found that the mRNA and protein level of FGF-2 in the RPE and RPE/choroidal tissues increased quickly within hours after a laser treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies about the role of FGF-2 in the de-velopment of CNV showed that FGF-2 can indirectly induce the neovascularisation formation via upregulation of VEGF and increasing the proliferation of endothelial cells [43][44][45] . Stahl et al [26] reported that combined inhibition of VEGF and FGF-2 was a superior therapy compared to single inhibition of VEGF in the treatment of CNV. Hu et al [27] found that the mRNA and protein level of FGF-2 in the RPE and RPE/choroidal tissues increased quickly within hours after a laser treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from VEGF, other pro-angiogenic factors like PDGF-β [17,24,25] , FGF [26][27][28][29] , TGF-β [17,[29][30][31][32] , and IL-8 [33][34][35][36] were also reported to be involved in the pathological process of AMD. Zehetner et al [24] compared the plasma levels of PDGF-β in neovascular AMD patients with healthy controls and found that there was a significantly higher plasma PDGF-β level in neovascular AMD patients than in healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…PDGF-DD inhibition thus attenuated the availability of multiple cellular components needed for pathological angiogenesis. In addition, PDGF-DD is a potent regulator of the expression of numerous proangiogenic and proapoptotic genes involved in pathological angiogenesis, such as VEGF, FGF2, PlGF, and VEGF-B, important players in CNV (25,(31)(32)(33)(34), Dcn and TNF-␣, apoptosis inducers and inhibitors of PDGF-induced vascular cell proliferation, migration, and survival (36 -39). Apoptosis occurs in the neovasculature during pathological angiogenesis (77,78).…”
Section: Discussionmentioning
confidence: 99%
“…3, A and B, n ϭ 8). These genes included fibroblast growth factor 2 (FGF2), vascular endothelial growth factor (VEGF), placental growth factor (PlGF), and VEGF-B, which play important roles in CNV (25,(31)(32)(33)(34). At day 3 after CNV, which is an early stage of CNV (35), the downregulation of the proangiogenic genes was moderate (Fig.…”
Section: Pdgf-dd Regulates the Expression Of Many Proangiogenic And Pmentioning
confidence: 99%
“…In contrast, FGF2 was more prevalent in CNV-RPE-69. FGF2 has been identified as a target for intravitreal therapy, especially in combination with anti-VEGF [27,28]. Neuropilin 1 has been associated with CNV formation [29][30][31], but was only upregulated in 1 CNV membrane.…”
Section: Discussionmentioning
confidence: 99%